Infant appendicitis with perforation: a case report - Fuad Adi Prasetyo; Ekvan Danang Setya; Supangat Supangat (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Appendicitis is one of the most common surgical emergencies in children. In the USA, there are 70,000 cases are diagnosed each year. Acute appendicitis is a rare case, barely considered in the diagnoses, and probably causes acute abdominal sepsis in neonates. It affects males generally 75% of the time and 25%-50% of all reported cases occur in premature infant. Almost 50 cases have been reported over the last 30 years. We reported a 5 month-old baby girl whom transferred to our hospital from a peripheral hospital. Previously, the baby diagnosis was low-type obstruction. At the time of admission to our hospital, the baby presented with a history of abdominal distension and did not pass stools after 48 h. Oxygen and oral gastric tube were administered. Exploratory laparotomy surgery was performed through a transverse incision. This report is a retrospective review of one patient with appendicitis perforation presented in our hospital.